Evaluación del comportamiento de la festuca (Festuca Arundinacea) con la aplicación de tres enmiendas orgánicas con tres diferentes dosis para el establecimiento de áreas verdes en la Universidad Técnica de Cotopaxi campus Salache 2023. - Quindigalle Vega, Nina Pacari (2023)
The importance of green areas is growing, since they are an important factor in the health and well-being of the inhabitant. The present investigation was carried out at the Technical University of Cotopaxi, Salache campus, with the objective of evaluating the behavior of the fescue (festuca arundinacea) with the application of three organic amendments with three different doses for the establishment of green areas at the Technical University of Cotopaxi. Campus Salache 2023. The work began with the cleaning and elimination of the kikuyu (Penissetum clandestinum), taking samples for soil analysis, later the area was marked and divided, thus leaving 4 repetitions or beds each divided into nine treatments and one witness. Subsequently, the incorporation of the amendments with their different doses was carried out. During the course of the work, the sprinkler irrigation system was fixed, having calibrated it for later use. In the month of December 2022, the fescue arundinacea was planted. In the course of the work, the following response variables were taken into account; germination percentage, coverage percentage, plant height at 25,30,35,40 and 45 days, number of leaves at 25,30,35,40 and 45 days, dry matter yield, analysis comparison initial and final soil chemical and costs. As results of the work, the T6 treatment (FERTIPLUS 2kg) It is the one that turned out best since it reached the highest percentages in terms of germination, obtaining a percentage of 76.25%. Regarding the percentage of coverage, obtaining a percentage of 72.5% coverage, it is also the one that presented the highest height of the plant 15cm at 45 days. The dry matter was calculated after each cut, as 3 cuts were made to the first cut, it was obtained that treatment No. 2 (NUTRIABOO 1.5KG) turns out to be more effective because it reached a percentage of dry matter of 40.51% at first cut. For the second cut, treatment No. 5 (FERTIPLUS 1.5KG) turns out to be more effective because it reached a percentage of dry matter of 40.42% at the second cut, while for the third and last cut it shows that treatment N °2 (NUTRIABONO 1.5KG) turns out to be more effective because it reached a percentage of dry matter of 54.15% at the third cut. Regarding the comparisons of the initial and final analysis, it was evident that there was not much difference in terms of elements, but in terms of organic matter, it can be said that its percentage increased since at the beginning it had 0.34% and in the final analysis 2.25% which is still very low. In production costs, a total expense of $291.85 was obtained, having this investment, since the implementation of green areas is recommended, even more so in educational institutions.